Secure Communication in Factories - Benchmarking Elliptic Curve Diffie-Hellman Key Exchange Implementations on an Embedded System - Gebauer, Lisa Helene; Trsek, Henning; Heiss, Stefan (2022 IEEE 18th International Conference on Factory Communication Systems (WFCS))
Securing factory communication to protect corporate data is an important concern in the context of the Industrial Internet of Things (IIoT). Various cryptographic protocols can be used to establish secure communication channels. One of these protocols is the Transport Layer Security 1.3 (TLS 1.3) protocol. A key component of the TLS handshake protocol is the Elliptic Curve Diffie-Hellman Key Exchange (ECDHKE), a public key cryptosystem used to exchange keys over insecure channels which can be based on a number of standardized elliptic curves. A special form of elliptic curves are Montgomery curves which are advantageous compared to more traditional Weierstrass curves due to their fast arithmetic. This is especially important when the ECDHKE is performed on embedded devices and in time-critical situations. In this work, the performance of ECDHKE implementations using standardized Montgomery curves Curve25519 and Curve448 included in the wolfSSL library are evaluated on an embedded 32-bit STM32L476RG Nucleo development board designed by STMicroelectronics. The benchmark results show that using Curve25519 with around 220ms for the key pair generation and the key agreement respectively is approximately 75% faster than using Curve448 with around 900ms for each of the algorithms, which can be attributed to their differing security levels. These results suggest that the algorithms might not be fast enough for time critical situations.
Keywords: secure; factory communication; elliptic curves; ECDHKE; performance; embedded

Investigation of Resource Constraints for the Automation of Industrial Security Risk Assessments - Ehrlich, Marco; Lukas, Georg; Trsek, Henning; Jasperneite, Jürgen; Diedrich, Christian (Workshop on Factory Communication Systems (WFCS))
The current static risk assessment processes and concepts do not match the increasing requirements with regard to flexibility within the industrial automation domain. The amount of manual tasks and needed efforts for risk assessments are too high in order to adequately cover the rising rate of system reconfigurations. Analysing the typical risk assessment processes from the IEC 62443 will show resource constraints with regard to time, bottlenecks, and the main cost drivers. If the most rewarding process steps can be identified and automated, the overall performance of risk assessments can be enhanced to keep up with the demanded flexibility.